2014
DOI: 10.1186/1743-0003-11-129
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergy stability and human balance maintenance

Abstract: BackgroundThe signals that the central nervous system (CNS) produces and sends to the muscles to effect movement are not entirely understood. Muscle synergy theory suggests that the central nervous system produces a small number of signals that pass through a network that distributes combinations of these signals to the muscles. Though these synergies are rather stable over time, some variability is present.MethodsHere, we investigated the variability of muscle synergy and defined a synergy stability index (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Moreover, electrophysiological studies have revealed the crucial role of motor cortical areas and of the corticospinal system in balance control 24,61,68 . Of note, postural responses involve the activation of muscle synergies throughout the entire body 15,6972 and the motor cortex plays an important role in activating these muscle synergies 7375 . A previous study with transcranial magnetic stimulation showed that a placebo procedure could influence the activity of the primary motor cortex, enhancing the excitability of the corticospinal system 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, electrophysiological studies have revealed the crucial role of motor cortical areas and of the corticospinal system in balance control 24,61,68 . Of note, postural responses involve the activation of muscle synergies throughout the entire body 15,6972 and the motor cortex plays an important role in activating these muscle synergies 7375 . A previous study with transcranial magnetic stimulation showed that a placebo procedure could influence the activity of the primary motor cortex, enhancing the excitability of the corticospinal system 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Although 92 muscles and 34 degrees of freedom were considered in the inverse dynamics calculations, due to the simplicity of the applied task (i.e., the fact that the lateral disturbance of a body standing upright can be simplified as a three-link inverted pendulum model (Jiang et al, 2002 ), and the selected quick and short time period to monitor both sensory and muscle data), we considered sensory synergy calculations using the lengths of the six dominant muscles for which EMG data were recorded are fair enough at this stage (Figure 3 ). Although it has been argued that the structure of synergies is dependent upon the number and choice of muscles included within the synergies analysis (Steele et al, 2013 ), we assume that the selected dominant muscles can cope with this issue since they have more influence in carrying out the concerned motion (Alnajjar et al, 2013b ; Wojtara et al, 2014 ). Adding other muscles for synergy calculations should not affect significantly the results (Steele et al, 2013 ), see also the Supplementary Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Fautrelle et al investigated the latencies of muscular activities and the way they are correlated between certain muscles to stress the muscular synergies involved in movement and, in their study, they suggested the CNS reprograms a new synergy after the target jumps in order to correct the ongoing reaching movement (Fautrelle et al, 2010). Wojtara et al proposed a synergy-based stability index during maintaining lateral balance, and this work considers the temporary muscle synergies in postural reflex and automatic response (Wojtara et al, 2014). Wang et al analyzed muscle synergies facing a step made with obstacles in elderly people and revealed a decreased ability to use multiple-mode synergies following a predictable perturbation (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%